2010
DOI: 10.1177/0363546510387507
|View full text |Cite
|
Sign up to set email alerts
|

Can the Reparability of Meniscal Tears Be Predicted With Magnetic Resonance Imaging?

Abstract: Background: Historically, magnetic resonance imaging (MRI) has been very useful in diagnosing meniscal tears but not as valuable in predicting whether a meniscal tear is reparable. Given that several recent studies suggested that MRI can be used to predict tear reparability, the topic has resurfaced as a controversy in the orthopaedic and radiology literatures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 15 publications
1
30
0
Order By: Relevance
“…This is likely because of a long-held belief that older patients have worse outcomes compared with younger patients after meniscal repair. 8,10 However, more recent studies have suggested that age may not play as significant a role in outcomes as previously believed. 21,31,36 Additionally, the role of obesity in meniscal repair outcomes has conflicting results in the literature, with a study by Brophy et al 9 showing significantly worse outcomes and higher rates of subsequent surgery rates in obese patients undergoing posterior medial root repairs.…”
Section: Discussionmentioning
confidence: 97%
“…This is likely because of a long-held belief that older patients have worse outcomes compared with younger patients after meniscal repair. 8,10 However, more recent studies have suggested that age may not play as significant a role in outcomes as previously believed. 21,31,36 Additionally, the role of obesity in meniscal repair outcomes has conflicting results in the literature, with a study by Brophy et al 9 showing significantly worse outcomes and higher rates of subsequent surgery rates in obese patients undergoing posterior medial root repairs.…”
Section: Discussionmentioning
confidence: 97%
“…17 Probably for this reason, a maximum distance of 3 mm from tear to meniscosynovial junction was chosen as criterion in other studies. 3,18,19 If we would have used this cut-off point of 3 mm in our study population, only 42.2% of the patients would have met this criterion. Matava and coworkers were uncertain about reparability of meniscal tears having a peripheral rim width of 3 to 5 mm, but they did not find those tears irreparable.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical criteria for meniscal repair include meniscal tears greater than 10 mm in length, unstable on probing, located within 3 mm of the meniscosynovial junction, involvement of greater than 50% of the thickness of the meniscus, and an intact peripheral body or inner meniscal fragment (37). With the above criteria, MR imaging yielded a mean accuracy of 60%-74%, sensitivity of 29%-47%, and specificity of 74%-89% in predicting whether a meniscal tear is reparable at surgery (37,38).…”
Section: Anterior Cruciate Ligament Injuriesmentioning
confidence: 99%